Pengembangan Koleksi Perpustakaan di Kantor Arsip, Perpustakaan, dan Dokumentasi Kota Padang - Silvia, Silvia; Rahmah, Elva (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2014)
This article discusses the development of library collections in the Archives Library and Documentation Padang. Panelitian method used through observation, interviews, and literature. Based on analyzing the data can be summarized as follows: First, the process of the development of library collections in the Archives Library and Documentation Padang form of procurement of library materials and the selection of library materials. Secondly, the constraints faced in conducting library collection development policy that is not in writing, not to have a special room to perform collection development, not maximum performance of librarians, and the lack of facilities and infrastructure. Third, should the Office of Library Archives and Documentation Padang has a written policy, has a special room to perform collection development, giving a clear assignment to any activity undertaken by a maximum librarians, particularly in library collection development activities, and Libraries Office of Library and Archives Padang documentation must consider infrastructure and facilities needed for all activities run smoothly. Keywords: development; collections; library collections; library